Synthesis and morphology evolution of indium nitride (InN) nanotubes and nanobelts by chemical vapor deposition. Issue 35 (14th August 2019) - Song, Wenqing; Si, Jiawei; Wu, Shaoteng; Hu, Zelin; Long, Linyun; Li, Tao; Gao, Xiang; Zhang, Lei; Zhu, Wenhui; Wang, Liancheng
Abstract : InN can form ternary alloys with Ga or Al, which increases the versatility of group-III nitride optoelectronic devices. Abstract : InN can form ternary alloys with Ga or Al, which increases the versatility of group-III nitride optoelectronic devices. However, more controllable InN chemical vapor deposition (CVD) growth is desired. Here, we report the growth of various InN nanostructures on silicon (100) using CVD by simply varying the growth temperature in a narrow range between 700 °C and 735 °C. X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDS) and transmission electron microscopy (TEM) confirmed the wurtzite crystallographic structure of the synthesized InN nanotubes (NTs) and nanobelts (NBs) with the preferential [0001] growth direction. A blue shift of the room temperature photoluminescence (RT-PL) spectra with the morphology evolution is observed. The growth mechanism and morphology evolution process of InN NTs and NBs are discussed. The temperature is revealed to be the main and quite sensitive factor affecting the morphological evolution. Our results are instructive for synthesizing InN and other nitride nanostructures.